DAMPAK KEBERADAAN INDUSTRI TERHADAP BUDAYA SANTRI DI KABUPATEN GRESIK - A.Syifaul Qulub (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The development of the industrial sector in Gresik Regency has experienced significant developments, regional statistical data states that during 2012 there were 512 new companies. The development of the industrial sector in Gresik Regency as part of the national development process in increasing economic growth has brought changes to people's lives. Changes due to industrial development, in addition to bringing prosperity to the Gresik community, also have an impact on the socio-economic and cultural aspects of the santri who grow and live with the community. The objective achieved in this study is to determine the impact of the existence of the industry in Gresik Regency on the socio-economic and cultural aspects of the santri. The study on the impact of the existence of the industry on the culture of santri in Gresik Regency was carried out using descriptive analysis research methods based on observations and studies of the cultural lethality of students in the Gresik community. Data collection (primary and secondary) is carried out by selecting, reading, studying, and researching books as well as conducting interviews with other reliable sources. The results of this research are that industrial development and development have led to socio-economic and socio-cultural changes for students in the Gresik community which have positive and negative impacts, namely; a) Socio-economic changes in the community include: changes in livelihoods, changes in the number of job opportunities, changes in income levels, and changes in the number of public facilities and infrastructure. b). The socio-cultural changes of the santri in the community include: the erosion of the santri culture in the Gresik community due to the new industrial culture. The positive impact on society is the creation of business and employment opportunities, namely the creation of wider business and employment opportunities for the community. Meanwhile, the negative impact on society is the erosion of the local Gresik culture, especially the santri culture which is replaced by a new industrial culture, due to the influence of the culture of industrial workers from outside Gresik and the dominance of industrial culture